Cash on Trial - Aleksander Berentsen; Nicole Jonker; Malte Krueger; Harry Leinonen; Katharina Linsbauer; Nikos Passas; Fabian Schär; Friederich Schneider; Paolo Tasca; Jens Ulbrich (SUERF - The European Money and Finance Forum, 2016)
Over millennia, mankind has used hard cash in various forms ranging from shells to gold coins and paper. More recently, cash has become unpopular in political circles, as it effectively restricts states' power to tax (explicitly or via negative interest rates) or to survey and potentially control their citizens. Several states have enacted restrictions to the use of hard cash. Above all, a strong new competitor to cash has arisen in the form of various electronic means of payment. Are we heading towards a society in which `coined freedom' (Dostojewski) will cease to exist? Under this provocative `motto' SUERF organised a combined evening event (in German at the University of Zurich) and one-day conference (in English at the theatre `Millers' in Zurich) to take stock of the arguments brought forward in the current debate on the pros and cons and, more generally, the future of cash.
Keywords: D12; E26; E41; E42; E43; E52; F24; G28; H26; K42; O17; O33; 330